Taxonomy of technological risks of open source software in the enterprise adoption context. (9th November 2015) - Silic, Mario; Back, Andrea; Silic, Dario
Abstract : Purpose: – The purpose of this paper is to identify the technological risks in the context of open source software (OSS) and suggest an integrative OSS risk taxonomy. Design/methodology/approach: – The authors conducted an extensive literature review followed by expert interviews and applied the method for taxonomy development. Findings: – This research has identified an integrative OSS risk taxonomy composed of 8 categories with 51 risk items. Originality/value: – This taxonomy is a very useful tool for practitioners during the decision-making process when evaluating, assessing and calculating risks related to OSS adoption. Moreover, researchers can use it as a starting point for future studies to better understand the OSS phenomenon.